University-community partnerships for promoting social responsibility in higher education - Sengupta, Enakshi; Blessinger, Patrick; Mahoney, Craig (Bingley, U.K. : Emerald Publishing Limited, 2020)
This book provides empirical evidence on how universities have considered social responsibilities as their prime focus, and engaged with civil society to enhance their values. Case studies from Indonesia to the United Kingdom enrich the book through experience, interventions and narratives.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Community and college; Educational sociology; Universities and colleges -- Sociological aspects; Education, Philosophy, Theory & Social Aspects; Colleges of higher education